2017
DOI: 10.1002/anie.201612231
|View full text |Cite
|
Sign up to set email alerts
|

The Borderline between Reactivity and Pre‐reactivity of Binary Mixtures of Gaseous Carboxylic Acids and Alcohols

Abstract: By mixing primary and secondary alcohols with carboxylic acids just before the supersonic expansion within pulsed Fourier transform microwave experiments, only the rotational spectrum of the ester has been observed. However, when formic acid was mixed with tertiary alcohols, adducts have been formed and their rotational spectra have been easily measured. Quantum mechanical calculations have been performed to interpret the experimental evidence. In the present study esterification takes place without catalyst.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Plenty of data have been obtained on the hydrogen‐bonded dimers involving proton tunneling, the Ubbelohde effect and conformational equilibria . HCOOH (formic acid; FA) is the prototype of the carboxylic acids family and for this reason it is involved in most of the investigations of carboxylic acids bonded to molecules containing other functional groups, such as its adducts with H 2 O, N(CH 3 ) 3 , CO 2 , the simplest aldehyde CH 2 O, the simplest amide H(CO)NH 2 , ethers, ketones, freons, azines and its reactivity with alcohols . An interesting feature of the dimer of FA, (FA) 2 , is the concerted transfer of the two hydroxylic protons, a motion in a double minimum potential.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Plenty of data have been obtained on the hydrogen‐bonded dimers involving proton tunneling, the Ubbelohde effect and conformational equilibria . HCOOH (formic acid; FA) is the prototype of the carboxylic acids family and for this reason it is involved in most of the investigations of carboxylic acids bonded to molecules containing other functional groups, such as its adducts with H 2 O, N(CH 3 ) 3 , CO 2 , the simplest aldehyde CH 2 O, the simplest amide H(CO)NH 2 , ethers, ketones, freons, azines and its reactivity with alcohols . An interesting feature of the dimer of FA, (FA) 2 , is the concerted transfer of the two hydroxylic protons, a motion in a double minimum potential.…”
Section: Figurementioning
confidence: 99%
“…[1] HCOOH (formic acid; FA)isthe prototype of the carboxylic acids family and for this reason it is involved in most of the investigations of carboxylic acids bonded to molecules containing other functional groups, such as its adducts with H 2 O, [2a] N(CH 3 ) 3 , [3] CO 2 , [4] thesimplest aldehyde CH 2 O, [5] thesimplest amide H(CO)NH 2 , [6] ethers, [7] ketones, [8] freons, [9] azines [10] and its reactivity with alcohols. [11] An interesting feature of the dimer of FA,( FA) 2 ,i st he concerted transfer of the two hydroxylic protons,amotion in ad ouble minimum potential. It can generate tunneling doubling observable in molecular spectra, and makes them useful to studies of the tunneling process.T he precise tunneling splittings (DE 01 )m easured by microwave (MW) spectroscopy for the acrylic acid dimer [1g] and for the formic acid-benzoic acid bi-molecule [1h] have been reproduced by model calculations with barriers at or close to values obtained ab initio.In Figure 1w es how the proton transfer motion in the formic acid dimer along as ymmetric double minimum potential energy profile.…”
mentioning
confidence: 99%
“…With water [4] and HCl, [5] the OH groups in alcohols have been found to act as proton acceptors,f orming OÀH···O or ClÀH···O HBs.W ith ammonia, [6] amines, [7] ethers, [8] and aldehydes, [9] the OH groups in alcohols act as proton donors. [11] Ar otationals tudy of the ethanol-cyclobutanonec omplex showedt hat the alcohol plays ad ual role as protond onor and acceptor, forming an etwork of one OÀH···O HB and two CÀH···O weakHBs. [10] In heterodimers, it seems that there is preference for the role of protond onor/acceptor:O nly two isomers with ethanolacceptor/methanol-donor structuresh ave been observed, which suggests ethanol-donor-methanol-acceptor interactions are energetically disfavored.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting observations have been made in the rotational spectra of the complexes formed between alcohols and carboxylic acids: By mixing primary and secondary alcohols with carboxylic acids just before the supersonic expansion only the rotational spectra of the esters, which are formed by gaseous esterification, were observed. However, when formic acid was mixed with tertiary alcohols, adducts were formed and their rotational spectra could be easily measured . A rotational study of the ethanol–cyclobutanone complex showed that the alcohol plays a dual role as proton donor and acceptor, forming a network of one O−H⋅⋅⋅O HB and two C−H⋅⋅⋅O weak HBs …”
Section: Introductionmentioning
confidence: 99%
“…We have to outline, however, that we came to this investigation accidentally. When trying to assign the pulsed jet Fourier transform microwave (FTMW) spectrum of the adduct FA-2-propanol by expanding a binary mixture of HCOOH and 2-propanol in He, we discovered that isopropylformate was formed by the esterification reaction instead . However, when HCOOH was in excess in the binary mixture, it was possible to observe and assign the rotational spectrum of FA-IPF.…”
Section: Introductionmentioning
confidence: 99%